Natural Enemies, Mediated by Landscape and Weather Conditions, Shape Response of the Sorghum Agroecosystem of North America to the Invasive Aphid Melanaphis sorghi - Brewer, Michael J.; Elliott, Norman C.; Esquivel, Isaac L.; Jacobson, Alana L.; Faris, Ashleigh M.; Szczepaniec, Adrianna; Elkins, Blake H.; Gordy, J. W.; Pekarcik, Adrian J.; Wang, Hsiao-Hsuan; Koralewski, Tomasz E.; Giles, Kristopher L.; et al. (Frontiers in Insect Science, 2022)
The sorghum (Sorghum bicolor [L.]) agroecosystem of North America provided an opportunity to evaluate agroecosystem response to an invading insect herbivore, Melanaphis sorghi (Theobald) (sorghum aphid) (previously published as Melanaphis sacchari Zehntner) (Hemiptera: Aphididae) onto a widely planted crop that experiences a range of agro-landscape and weather conditions. Initial sorghum risk assessments after M. sorghi's invasion in the mid-2010s provided forecasts of range expansion and annual migration, which were based on aphid life history, extent of sorghum cultivation and susceptibility to M. sorghi, and weather (aphid-plant-weather [APW] risk scenario). A more comprehensive risk assessment proposed here brings top-down forces of M. sorghi-natural enemy interactions to the forefront as mediated by agro-landscape and weather conditions (aphid-enemy/landscape-weather mediated [AE/LW] risk scenario). A hypothesis of regional differences in aphids and natural enemies and sensitivity to agro-landscape and weather was tested using empirical data of insect, landscape, and weather data across 5 years and four regions (two in the U.S. Great Plains [South GP and North GP], one farther south (South), and one in the southeast U.S. [South E]). Natural enemies were widespread with two parasitoids and four coccinellid species common across regions, but regional variation in M. sorghi and natural enemy abundance was detected. The AE/LW risk scenario accounted for natural enemy abundance and activity that was highest in the South region, functioned well across agro-landscape and weather conditions, and was accompanied by average low M. sorghi abundance ( 23 M. sorghi per leaf). Positive correlations of natural enemy-M. sorghi abundance also occurred in the South GP region where M. sorghi abundance was low ( 20 M. sorghi per leaf), and selected natural enemy activity appeared to be mediated by landscape composition. Melanaphis sorghi abundance was highest in the South E region ( 136 aphids/leaf) where natural enemy activity was low and influenced by weather. The AE/LW risk scenario appeared suited, and essential in the South region, in assessing risk on a regional scale, and sets the stage for further modeling to generate estimates of the degree of influence of natural enemies under varying agro-landscape and weather conditions considered in the AE/LW risk scenario. Broadly, these findings are relevant in understanding agroecosystem resilience and recommending supportive management inputs in response to insect invasions in context of natural enemy activity and varied environmental conditions.